Unrivaled - Noël, Alyson (Noël, Alyson. Beautiful idols novel., 2016)
"Aspiring reporter Layla, budding actress Aster, and future guitar hero Tommy find themselves with a VIP invite to the world of Los Angeles's nightlife and lured into a competition where Hollywood's hottest starlet, Madison Brooks, is the target. Just as their hopes begin to gleam like stars through the California smog, Madison Brooks goes missing"--